2014
DOI: 10.1016/j.buildenv.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of thermo-hygrometric conditions of an archaeological site affected by unlike boundary weather conditions

Abstract: ElsevierMerello Giménez, P.; Fernández Navajas, Á.; Jorge Curiel-Esparza; Zarzo Castelló, M.; García Diego, FJ. (2014). Characterisation of thermo-hygrometric conditions of an archaeological site affected by unlike boundary weather conditions. Building and Environment. 76:125-133. doi:10.1016/j.buildenv.2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…HtA and Tr appeared as the most relevant stages for the sensor discrimination. This result is consistent with a previous research [ 5 ], which reported a pronounced temperature gradient at the museum, particularly in summer, caused by the greenhouse effect of the skylight. The identification of the key stages of the time series for discriminating the sensors might help to select and enhance the criteria of adequate sampling intervals in automated systems for microclimate monitoring.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…HtA and Tr appeared as the most relevant stages for the sensor discrimination. This result is consistent with a previous research [ 5 ], which reported a pronounced temperature gradient at the museum, particularly in summer, caused by the greenhouse effect of the skylight. The identification of the key stages of the time series for discriminating the sensors might help to select and enhance the criteria of adequate sampling intervals in automated systems for microclimate monitoring.…”
Section: Resultssupporting
confidence: 94%
“…To replace the beneficial effect of the water layer, a provisional canvas cover was installed directly over the skylight, in order to avoid the overheating of the archaeological site below, by preventing direct sunlight. A second thermo-hygrometric monitoring study was performed in 2011 to assess the effect of different corrective measures and changes implemented in the museum [ 5 ]. The microclimatic data of RH and T recorded in 2010 before laying the canvas cover was compared with air conditions in 2013, after its installation.…”
Section: Introductionmentioning
confidence: 99%
“…Actions within the framework of preventive conservation [40] imply the definition of an effective and systematic methodology to identify [38], evaluate and control the threats that affect all cultural assets [41][42][43][44][45][46]. The aim of these actions is to minimize these threats [47][48][49][50], thanks to the evaluation of their degree of impact on the effects of deterioration and the development of appropriate measures to avoid or, at least, slow down their negative effects [39,51].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in the case of monitoring cultural heritage, historical data (without underestimating real-time alarms, etc. ) is more interesting as it is important to characterise the site for performing comparative studies in the future, either regularly, in order to verify whether the conditions are constant, or occasionally, when the boundary conditions are altered [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them use individual data-loggers. Some authors [ 16 ] use Hobo data-loggers [ 17 ], and other studies [ 6 , 11 , 18 ] work with data-loggers DS1922L [ 19 ] and DS1923 [ 20 ]. Data from these data-loggers cannot be sent automatically to the cloud and due to they are commercial devices, its hardware and software is unknown and cannot be modified.…”
Section: Introductionmentioning
confidence: 99%